Thiamine Responsive Poli-oencephalomalacia in a Swan Goose- A Case Report - Digraskar, S.U.; Borikar, S.T.; Tawheed, A.S.; Nithin, B.S.; Neelam, S.; Kumbhar, S. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Thiamine (vitamin B1) deficiency in birds is caused by malnutrition or thiaminase-rich foods (raw freshwater fish) or foods high in anti-thiamine factors (betel nuts).Thiamine is an essential water soluble vitamin contributing phosphate derivatives that are involved in many cellular processes as coenzymes in the catabolism of sugars and amino acids. Also thiamine triphosphate (TTP) helps in proper functioning of neuronal membranes (Cooper and Pincus, 1979) and its deficiency leads to polyneuritis which is manifested as lethargy, head tremors, impaired digestion, general weakness, star-gazing and frequent convulsions (Aiello, 2016; Susan, 2016).